2006
DOI: 10.1007/s10705-006-9000-7
|View full text |Cite
|
Sign up to set email alerts
|

N2O and NO emission from agricultural fields and soils under natural vegetation: summarizing available measurement data and modeling of global annual emissions

Abstract: The number of published N 2 O and NO emissions measurements is increasing steadily, providing additional information about driving factors of these emissions and allowing an improvement of statistical N-emission models. We summarized information from 1008 N 2 O and 189 NO emission measurements for agricultural fields, and 207 N 2 O and 210 NO measurements for soils under natural vegetation. The factors that significantly influence agricultural N 2 O emissions were N application rate, crop type, fertilizer type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
748
21
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 887 publications
(847 citation statements)
references
References 37 publications
46
748
21
10
Order By: Relevance
“…One driving force of N 2 O emission is the intensity of N fertilisation. Numerous studies have reported the relationship between N 2 O emission and mineral and organic N fertilisation [52][53][54]. However, in this study, an effect of fertilisation on N 2 O emissions could not be observed for the full study period, probably due to relatively low fertilisation rates of maximum 75 kg N ha −1 with a high variability.…”
Section: Driving Forces Of Ghg Emissions In Srccontrasting
confidence: 61%
“…One driving force of N 2 O emission is the intensity of N fertilisation. Numerous studies have reported the relationship between N 2 O emission and mineral and organic N fertilisation [52][53][54]. However, in this study, an effect of fertilisation on N 2 O emissions could not be observed for the full study period, probably due to relatively low fertilisation rates of maximum 75 kg N ha −1 with a high variability.…”
Section: Driving Forces Of Ghg Emissions In Srccontrasting
confidence: 61%
“…Moreover, in many studies fertilizer N source effects are confounded with placement and other variations in methodology, thus further complicating (and often invalidating) comparisons of N source effects. Using an expansion of the data set used by Bouwman et al (2002a), Stehfest and Bouwman (2006) found that after balancing for other factors, differences among fertilizer types all but disappeared. On the other hand, there is growing evidence that enhancedefficiency fertilizers such as slow and controlled release and stabilized N fertilizers can enhance crop recovery of fertilizer N and minimize nutrient losses to the environment (Snyder et al 2007).…”
Section: Fertilizer N Typementioning
confidence: 99%
“…whether NBPT or DCD was incorporated into the granule). Other studies have also found N 2 O emissions were greater from NO 3 --based fertilisers than from urea (Dobbie and Smith 2003, Stehfest and Bouwman 2006, Kuikman et al, 2006. The range of direct annual EFs in this experiment (0.02-3.81%) are similar to the ranges of EFs calculated by Dobbie and Smith (2003) in Scottish grasslands (1 to 3%), Kuikman et al, (2006) (Hyde et al, 2006, Rafique et al, 2011).…”
Section: N 2 O Emission Factorsmentioning
confidence: 94%